Socioeconomics of the Lionfish Derby Fishery - Trotta, Kristina Ann; Nardelli, Adam; Green, Stephanie; Akins, L.; Kerstetter, David W. (NSUWorks, 2014)
Throughout the western North Atlantic Ocean, Caribbean Sea, and the Gulf of Mexico, invasive Indo-Pacific lionfish (Pterois volitans/ miles complex) have established dense populations, greatly impacting their host environments. Resource managers across the adopted range are working to develop strategies to minimize the destruction being caused by these fish. Lionfish tournaments – single-day events where competitors aim to collect and remove as many lionfish as possible – have been an important tool in suppressing local populations of lionfish. As understanding increases of the potential of these events to control the lionfish population, they are becoming an increasingly important tool for resource managers and other concerned stakeholders. Tournaments can also bring economic benefits to the communities where they are held, although this impact has yet to be formally studied. Participants at two recent South Florida derby events were interviewed on site, using a six-page survey asking them to describe (1) the lionfish derby experience; (2) non-derby related lionfish removal effort; (3) derby expenditures; and (4) personal characteristics. Respondents spent approximately $500 per person, including expenditures nominally related to the event, such as hotel rooms and restaurant meals, creating a net benefit to the communities where they were held. Additional lionfish derby events will be surveyed to develop a more complete picture of their socioeconomic characteristics. In addition to the analyses of these individually surveyed derby events, historical participation data will be used to place the surveyed events within the context of the overall lionfish derby fishery as a whole.